ANALISIS ANOMALI PASAR EFISIEN TERHADAP RETURN SAHAM PADA INDEKS HARGA SAHAM GABUNGAN DAN INDEKS HARGA SAHAM GLOBAL - Franciskus Jumintang (2022)
Market anomaly is a phenomenon that occurs in the market. In anomaly should not be found in markets that are considered efficient. An anomaly is an aberration in efficient market theory where existing information does not reflect stock prices, so investors can earn abnormal returns. The research objectives was to see how The Day Of The Week Effect and The Month Of The Year Effect affect stock returns on the Indonesian Stock Price Index and the Global Stock Price Index. The samples in the study were daily stock return data and return data on stocks of IHSG, DJIA, SSEC, and N225. The Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model is used to analyze data. The results showed that in IHSG and SSEC there was no The Day Of The Week Effect. The DJIA and N225 found The Day of the Week Effect. The Month of the Year Effect was found in IHSG, DJIA, SSEC, and N225. Keywords : GARCH, market anomaly, market hyphothesis, the day of the week effect, the month of the year effect.